Catalytic enantioselective bromohydroxylation of aryl olefins with flexible functionalities. Issue 6 (2nd March 2017) - Li, Jing; Li, Zequan; Zhang, Xun; Xu, Bing; Shi, Yian
Abstract : A highly enantioselective bromohydroxylation of aryl olefins with flexible functionalities has been achieved with (DHQD)2 PHAL as a catalyst and H2 O as a nucleophile, giving a variety of optically active bromohydrins with up to 98% ee. Abstract : A highly enantioselective bromohydroxylation of aryl olefins with flexible functionalities has been achieved with (DHQD)2 PHAL as a catalyst and H2 O as a nucleophile, giving a variety of optically active bromohydrins with up to 98% ee. An acid additive has been found to be beneficial for the reactivity and enantioselectivity.